PENGARUH PEMBERIAN BUAH PEPAYA (CARICA PAPAYA L) TERHADAP KADAR KOLESTEROL TOTAL PADA TIKUS SPRAGUE DAWLEY DENGAN HIPERKOLESTEROLEMIA - Dewi, Claudia Kartika; Probosari, Enny (Journal of Nutrition College, 2012)
ABSTRACTBackground : Coronary Heart Disease (CHD) is a cardiovascular disease wich primary cause of deadness in any countries. It is one of the causes hypercholesterolemia. Papaya fruit has many benefits for health such as anti-inflammatory, anti-hypertension, it can reduce triglyceride levels and it can reduce total cholesterol levels in the blood. The purpose of this study is to investigate the effect of administration of papaya (Carica papaya L) for total cholesterol levels in Sprague Dawley rats with hypercholesterolemia.Method : This research was true-experimental pre-post test control with rondomized group design. Subjects were male Sprague Dawley rats aged 7-8 weeks, weight 100-200 grams are a given blended of papaya fruit as much as 5.4 g, 7.2 g and 9.0 g per within 4 weeks. Total cholesterol levels are determined by the CHOD-PAP method Enzimatic Precipitation Colorimeter Test. Data normality was tested by Shapiro Wilks. Data were analyzed by ANOVA test, followed by LSD test.Result : the research shows that giving papaya 5.4 g per day is able to reduce total cholesterol were significantly (p = 0.001). Giving papaya in dosage of 7,2 g can reduce cholesterol but it is insignificance (p= 0,086) and giving papaya in dosage of 9,0 g can not reduce the cholesterol (p= 1,000).Conclusion : Giving papaya dosage 5.4 gr, 7.2 g and 9 g can not lower significantly of total cholesterol levels Key Words : hypercholesterolemia, papaya, total cholesterol